Technology based ludic activities and its influence on oral production in 1st year students B.G.U. at Centro Educativo Naciones Unidas, school year 2019-2020 - Espinoza Vega, Cristina Belén (2020)
In this work paper, the technological based ludic activities include tasks that are done before, during and after the oral production process takes place. Through the proper application of these activities, students who love to speak, demonstrate their maximum capacity of communication, production, fluency and accuracy of the task. One of the main reasons the topic of technological ludic activities has importance is because the teacher should make a preliminary analysis, approaching it in a psychological and didactic way. This prior knowledge, acquired before presenting it to the students, is assimilated through daily living. The ludic activities include games and materials that may be associated with the task. Therefore, personal experiences related with what are stated in the task, and the knowledge that it provides is easily and ludic adapted. This pre-knowledge makes students understand the topic, incorporates personal experiences, which will make the activities attractive, understandable and memorable……